Economic determinants of public support for European integration, 1995–2018. (June 2021) - Foster, Chase; Frieden, Jeffry
European support for integration is shaped by a range of economic, cultural, and political factors. However, in recent decades, scholars have argued that utilitarian calculations have become less important as European integration has advanced, and political entrepreneurs have mobilized nationalist identities. We analyze 24 years of responses to the Eurobarometer (1995–2018) to assess the influence of economic factors on public attitudes toward European integration. We find strong evidence that utilitarian factors are important across the entire panel. The performance of the macro-economy, as measured by unemployment, and an individual's position in the labor market, are consistent predictors of public support for and satisfaction with the European Union. Collective identity is also associated with attitudes toward the European Union. However, an individual's identity is also shaped by economic circumstances.